2021
DOI: 10.1590/s1677-5538.ibju.2019.0766
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study comparing bipolar plasmakinetic transurethral resection of the prostate and monopolar transurethral resection of the prostate for the treatment of Benign Prostatic Hyperplasia: efficacy, sexual function, Quality of Life, and complications

Abstract: Objective: To generate high-quality data comparing the clinical effi cacy and safety profi le between monopolar transurethral resection of the prostate (M-TURP) and bipolar plasmakinetic resection of the prostate (PK-TURP) for benign prostatic hyperplasia (BPH). Materials and Methods: Prospective, randomized, single-blinded study conducted in a tertiary-care public institution (Dec/2014-Aug/2016). Inclusion criteria: prostate of <80g in patients with drug-refractory lower urinary tract symptoms (LUTS), complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…However, other potential risk factors such as PSA density, PSA velocity, or underlying diseases could not be investigated due to the limited data obtained from the included studies. Nevertheless, one previous research indicated that higher preoperative PSA density and velocity, preoperative treatment with 5-alpha reductase inhibitors, and diabetes was identified to have a significant correlation with the diagnosis of IPC after surgery for BPH (41)(42)(43)(44). Future study regarding more important risk factors of IPC with sufficient data are still needed for early screening and identification of IPC patients.…”
Section: Implications For Clinical Practicementioning
confidence: 97%
“…However, other potential risk factors such as PSA density, PSA velocity, or underlying diseases could not be investigated due to the limited data obtained from the included studies. Nevertheless, one previous research indicated that higher preoperative PSA density and velocity, preoperative treatment with 5-alpha reductase inhibitors, and diabetes was identified to have a significant correlation with the diagnosis of IPC after surgery for BPH (41)(42)(43)(44). Future study regarding more important risk factors of IPC with sufficient data are still needed for early screening and identification of IPC patients.…”
Section: Implications For Clinical Practicementioning
confidence: 97%
“…16 Furthermore, urinary tract infection is a common perioperative complication following TURP that may occur in 1.7-8.2% of patients; however, two patients (25%) in this case series reported UTI. [17][18][19] Moreover, urethral stricture may occur following TURP because of the large resectoscope sheath, which may cause urethral ischemia and/or trauma. 17 In this setting, one patient developed urethral stenosis 12 months after the surgery that was managed by optical urethrotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The study population was retrieved from NCT03936244 randomized clinical trial (RCT), which included men diagnosed with lower urinary tract symptoms (LUTS) in a tertiary-care public institution who required surgical treatment and were randomly allocated to monopolar or plasmakinetic TURP. Additional details on the trial are available in the original publication [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…IIEF-5 questionnaire scores (Supplementary Table 1) were recorded for all patients at baseline and 1, 3, 6, and 12 months postoperatively [7]. Two additional questions were included at every period: one to capture sexual activity as self-reported by patients (a yes/no question); and another one to capture the reason for sexual inactivity as reported by the patients [possible answers were either "Inability to penetrate (enter) the partner due to penile flaccidity" or "Other causes (e.g., lack of sexual desire, lack of a sexual partner, etc.)"].…”
Section: Methodsmentioning
confidence: 99%